2006
DOI: 10.1086/508428
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Phagocytosis of NontypeableHaemophilus influenzaeby Human Alveolar Macrophages in Chronic Obstructive Pulmonary Disease

Abstract: These results support a paradigm of impaired phagocytosis by alveolar macrophages, but not blood macrophages, in COPD and provide an immunologic basis for persistence of NTHI in the airways of adults with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
5
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 37 publications
9
161
5
2
Order By: Relevance
“…This may also explain why all the receptors investigated were Chana 18 at lower levels on macrophages isolated from COPD lung compared to controls and may contribute to reduced phagocytosis reported for COPD macrophages 44,45 .…”
Section: Discussionmentioning
confidence: 93%
“…This may also explain why all the receptors investigated were Chana 18 at lower levels on macrophages isolated from COPD lung compared to controls and may contribute to reduced phagocytosis reported for COPD macrophages 44,45 .…”
Section: Discussionmentioning
confidence: 93%
“…Others have suggested that alveolar macrophage phagocytic ability might be diminished in subjects with COPD. 16,26 Macrophages also elicit inflammatory responses through production and secretion of cytokines/chemokines. We found that at 1 week, macrophages differentiated in the presence of organic dust can still release TNFα, IL-6, IL-10, CXL8 when restimulated with high dose ODE, but when compared to non-dust treated cells (control), the secretion of TNFα, IL-6, IL-10 was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of smokers with COPD to respiratory infections is greater than that of nonsmokers, because CS exposure causes several disruptions to the innate lung defenses, such as impairment of mucociliary clearance [125], reductions in ciliary beat frequency and in the numbers of ciliated cells due to squamous metaplasia [126], reduction in the concentrations of surfactant proteins A and D [127], salivary lysozyme and sputum secretory leukocyte protease inhibitor deficiency [128,129], and impairment of phagocytosis by alveolar macrophages [130,131] (Figure 4). In addition, even a stable COPD condition is associated with respiratory pathogens in the airways, which worsens airflow conductance [132,133] and triggers an inflammatory response [15,123,[134][135][136] and presence of inflammatory markers in sputum [133,[137][138][139].…”
Section: Copd Exacerbationsmentioning
confidence: 99%